Ibiebe Alphabet and Ideograms as Motifs for Fabric Embellishment - Ajiginni, Margaret; Olumide, Bakare Olayinka (Advances in Social Sciences Research Journal, 2021)
The invented Bruce Onobrakpeya’s Ibiebe alphabet and ideogram (writing system) have not been explored maximally and redesigned as recurring motifs to embellish contemporary fabric. These are artistic codified graphical images that represent the visual translation of myths, legends, ideal concepts, and the philosophies of the Urhobo cultural heritage from Delta State. They are mostly explored in paintings and sculptural pieces for aesthetic and refinement purposes. Whereas, it is pertinent to encourage the integration of the creative potential of indigenous culture as visual concepts into contemporary works, since art is a potent medium for cultural dialogue. Therefore, this paper seeks to redesign the versatility and ingenuity embedded in Bruce Onobrakpeya’s formation as a recurring motif for fabric embellishment. It is essentially to provoke creativity, the development of knowledge, skills, in-studio experimentation/exploration, and the creation of new design possibilities with a diverse visual relationship. The Aesthetic theory propounded by Alexander Gottlieb Baumgarten (1714-1762) and the Modern Creativity theory by Kanematsu, H. and Barry, D. M. (2016) were adopted. The approach is exploratory and descriptive and relies on literal information. It will serve as an encyclopedia of redesigned motifs that cut across visual history.